The effect of corporate governance on the financial performance of listed financial institutions in Ghana - ANSAH LUCAS BISSALA (KNUST, 2024)
A thesis submitted to the department of accounting and finance, institute of distance learning, Kwame Nkrumah university of science and technology, in partial fulfilment of the requirements for the degree of master of science (accounting and finance). Knust school of business (ksb) college of humanities and social sciences